A review on the evolvement of optical-frequency filtering in photonic devices in 2016–2021. (June 2022) - Pan, Hong-Yu; Chen, Xue; Xia, Xin-Lin
Abstract: In photonic devices, the optical filter plays an essential role by steering the electromagnetic wave in optical frequency to reshape the spectrum. However, suffering from the imperfect-matching problem of the target with the actual spectrum, the energy conversion efficiency of photovoltaic devices still cannot meet the satisfactory level. Herein, the recent striking development of the optical filter is reviewed and several proper approaches of improving in the future is hypothesized. On-going performance improvements are expected, as well as a rapidly growing understanding of the fundamental principles in photoelectric conversion. In the first instance, staring from the realization of optical filters, novel means getting benefit from the micro-nanotechnology are introduced in various classes by their feathers, respectively. The introduction consists of the periodic surface micro-nanostructure, metamaterial, metasurface, fluid filters and reasonable evaluation are given based on the researches from 2016 to 2021. Subsequently, the applications of optical filters are enumerated, the characteristics are evaluated and the development potential is proposed in specific fields. For both of conventional applications (such as photovoltaic cells, photovoltaic/thermal systems, thermophotovoltaic systems, etc.) and burgeoning ones (such as radiant cooling, spectral stealth, ultraviolet defending, etc.), their unique optical filters are functioned ingeniously to minimize the energy loss in different ways. In addition, the measurements of their optical properties are briefly introduced at room temperature and high temperature. Finally, to promote the development of high-efficiency photonic devices and meet current challenges, the corresponding improvement suggestions are discussed for the practical application of large-area, ultrawide-spectrum and high-efficiency photonic devices. Graphical abstract: Image 1 Highlights: This work comprehensively summarizes the development of optical filtering technology on photonic devices in the period of 2016–2021. Due to the wide application of nanotechnology, optical filters are analyzed and evaluated, including different implementation methods and various photonic applications respectively. The existing problems of optical filters and the possible improvement directions in the future are put forward in this work.